(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
This research focuses on the study of the transformation of community business, based on widely accepted community business in Japan that receives a lot of successes in creating and adapting the business model that fits the people’s behavior and social trend for years. Therefore, this research was aimed to explore business models of Japanese community businesses to find the factors leading to their success and failure. Additionally, an in-depth study was also done in a selected community business to draw insights which could be used to create recommendations for other businesses who might be looking for a way to solve similar problems. The exploratory research conducted in this study showed that to fulfil sustainability goals, 4 types of stakeholders new and old generations, government, and tourists, need to contribute and own a shared value which is “Tradition and Sense of Belonging” as the followings.1)Old Generation is a group of the locals sharing commitment to present culture and traditional crafting knowledge which are the core service of this business.2)New Generation can take challenges and be adaptable to modern community which will make immense contribution to leading traditional business to the future.3)Government needs to share the decision-making authority with people, which will provide the locals a sense of belonging.4)Tourists can be engaged with the community in the deep level through services that provide a sense of belonging. Tourists should be invited to be part of the community, despite a short period of time.The insights drawn from this study were used to develop the recommendations which could be used by other communities with similar societal context in their transformation effort, and business model development.